Thymidylate synthase inhibitory drugs induce p53-dependent pathways differently - Eszter Holub; Milda Blanka Szajkó; Anna Felföldi; Beáta G. Vértessy; Angéla Békési (PLoS ONE, 2026)
Thymidylate synthase (TS) is a key enzyme in thymidylate biosynthesis and an established target of chemotherapeutics such as 5-fluoro-2’-deoxyuridine (5FdUR) and raltitrexed (RTX). Inhibition of TS disrupts the dUTP:dTTP balance, leading to uracil misincorporation, triggering futile base excision repair cycles, DNA strand breaks, and ultimately cell death. Interestingly, when the main uracil-DNA repair pathway is inhibited, treatment with TS-inhibitory drugs still leads to cell death. Beyond its catalytic role, TS also binds RNA, autoregulating its own translation and interacting with transcripts such as p53 and c-Myc, thereby linking TS activity to broader post-transcriptional regulatory networks. These interactions, together with regulation by miRNAs and lncRNAs, suggest that TS inhibition may provoke cellular responses extending beyond DNA metabolism. To explore these mechanisms, we investigated the transcriptomic effects of TS inhibition with either 5FdUR or RTX in wild-type HCT116 and two HCT116-derived cell lines with different capacities in base excision and mismatch repair pathways. Both drugs induced DNA damage responses yet displayed distinct transcriptional signatures. A strong 5FdUR-biased induction of mRNAs corresponding to p53-related pathways was detected in all cell lines and further validated with qPCR and Western blot. Moreover, co-immunoprecipitation coupled to sequencing revealed direct RNA partners of TS, highlighting its possible post-transcriptional regulatory role. Our findings underscore the multifaceted impact of TS inhibition, linking enzymatic disruption to RNA-level regulation and revealing drug-specific differences in cellular responses.